Peran Pendidikan Agama Islam Dalam Membentuk Etika Digital Siswa Generasi Z Melalui Literasi Digital Berbasis Nilai-Nilai Islam - Andika Fisabilla (EL-EMIR Institute, 2026)
The rapid development of digital technology has transformed various aspects of human life, including education. Generation Z, which was born and raised in the digital era, has a very high level of technology usage. Although technology provides many benefits in learning, easy access to information also creates challenges such as misinformation, cyberbullying, social media addiction, and declining digital communication ethics. This study aims to analyze the role of Islamic Religious Education in shaping the digital ethics of Generation Z students through Islamic value-based digital literacy. The research employs a library research approach by reviewing relevant scientific journals, books, and academic documents. The findings reveal that Islamic Religious Education plays a strategic role in fostering digital ethics through the internalization of honesty (ṣidq), responsibility (amanah), verification (tabayyun), respectful communication, and self-control in technology usage. These values are implemented through classroom learning, teacher role modeling, positive digital habits, and strengthening Islamic digital literacy. Therefore, Islamic Religious Education serves as an important instrument in developing a digitally competent generation with strong moral character.